2014 IEEE 41st International Conference on Plasma Sciences (ICOPS) Held With 2014 IEEE International Conference on High-Power P 2014
DOI: 10.1109/plasma.2014.7012761
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model of suppression of electron instability in hall thrusters by boundary feedback system

Abstract: Among plasma instabilities in Hall thrusters, large-scale electron instability of Rayleigh type holds one of the main positions. Its arising brings about redistribution of the electrical field in the acceleration layer that can increase losses of ions on the walls of the thruster. In the paper, the possibility of suppression of this instability by a boundary feedback system (BFS) is theoretically considered. The analysis is carried out with the use of hydrodynamic approximation. The eigenvalue problem is solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…The proposed approach is significantly different from most known works [1,2,[4][5][6][7]11] in this scientific field. In them, the main attention is paid to the formal construction of mathematical models of fluctuations of plasma parameters in Hall thrusters and mathematical modeling without specific reference to the integral parameters of the thruster -thrust, specific impulse, efficiency.…”
Section: Discussion Of Results Of Investigating Discharge Current Osc...contrasting
confidence: 57%
See 2 more Smart Citations
“…The proposed approach is significantly different from most known works [1,2,[4][5][6][7]11] in this scientific field. In them, the main attention is paid to the formal construction of mathematical models of fluctuations of plasma parameters in Hall thrusters and mathematical modeling without specific reference to the integral parameters of the thruster -thrust, specific impulse, efficiency.…”
Section: Discussion Of Results Of Investigating Discharge Current Osc...contrasting
confidence: 57%
“…On the basis of a critical analysis of existing works [1][2][3][4][5][6][7][8][9][10][11] tackling the problem of the occurrence of significant discharge current fluctuations in Hall thrusters, it is shown that their formation leads to a significant decrease in the main values of the thruster parameters -thrust, specific impulse, and efficiency. Thus, this issue has not yet been solved, and all Hall thruster developers face this problem.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation